2019
DOI: 10.3928/01477447-20190118-05
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral Joint Contact Pressures: Current Concepts and Use in Patellar Instability Studies

Abstract: The patellofemoral joint is thought to be a common source for knee pain. Improper alignment and function of the patellofemoral joint can lead to abnormal contact pressures, which may explain patients' symptoms. In this review, the authors examine techniques for measuring patellofemoral joint contact pressures and summarize the relevant patellofemoral joint anatomy and contact pressures in normal knee kinematics. Finally, they discuss the results of studies investigating contact pressure changes in cases of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…However, despite the improvement of patella tracking, complete restoration to physiological alignment did not occur. The present results are in line with those of a variety of other studies, even though comparism of the actual values to those in the other studies is limited due to the use of diferent examination techniques [22,30,34]. Isometric muscle contractions revealed slightly larger patellofemoral contact areas than did the absence of muscular activity, conirming trends reported in previously published studies, although Gold et al reported considerably larger contact areas [6].…”
Section: Discussionsupporting
confidence: 91%
“…However, despite the improvement of patella tracking, complete restoration to physiological alignment did not occur. The present results are in line with those of a variety of other studies, even though comparism of the actual values to those in the other studies is limited due to the use of diferent examination techniques [22,30,34]. Isometric muscle contractions revealed slightly larger patellofemoral contact areas than did the absence of muscular activity, conirming trends reported in previously published studies, although Gold et al reported considerably larger contact areas [6].…”
Section: Discussionsupporting
confidence: 91%
“…By midflexion, concerns of instability caused by graft loosening were somewhat mitigated by the degree of constraint provided to the patella by the anatomy of the trochlear groove, although this can vary depending on the degree of patella alta and trochlea dysplasia. 20,36 The adductor sling and adductor transfer techniques were significantly more anisometric with these grafts tightening as the knee flexed. Graft tightening can lead to loss of ROM, pain, graft stretching, and, ultimately, graft failure with future recurrent instability.…”
Section: Discussionmentioning
confidence: 99%
“…The increased access to the joint in this approach greatly simplifies measurements of patellar kinematics using optical [32,33] or other [34,35] motion tracking techniques. Contact forces and pressure can be measured in vitro through the use of pressure-sensitive films [36][37][38]. Mechanical stability of the patellofemoral joint can also be quantified by applying a force to the patella and measuring the resulting displacement [35,39,40].…”
Section: In Vitromentioning
confidence: 99%